Adenomyosis: What is New?. (September 2015) - Senturk, Levent M; Imamoglu, Metehan
Adenomyosis is described as the benign invasion of endometrium into the myometrium, with endometrial glands and stroma surrounded by the hypertrophic and hyperplastic myometrium. It may affect 20% of female population and most widely seen among perimenopausal and multiparous women. Its etiopathogenesis, diagnosis, clinical findings and current various treatment options will be discussed in this article.